Variations of the metabolome in the digestive system of Antarctic krill, Euphausia superba, between summer and autumn - Simone Heyen; Verena Töpker; Bernd Kopke; Nevenka Cakić; Lukas Hüppe; Bettina Meyer; Heinz Wilkes (PLoS ONE, 2025)
Rapid climate change threatens the relatively pristine environment of the Southern Ocean. The effects on biogeochemical cycles and their subsequent consequences for the organisms in this area are of significant interest. Antarctic krill, Euphausia superba, is the dominant species in the Antarctic ecosystem and a vital component of the Southern Ocean food web. Its metabolism is influenced by the feeding regime, which is governed by environmental conditions. However, little is yet known about the metabolome of Antarctic krill. Here, we investigated metabolite classes that can serve as tracers for documenting variations in the metabolic and biochemical status of krill. To this end, we utilised targeted metabolomics to analyse coenzyme A thioesters, amino acids, B vitamins, and respiratory quinones in the digestive system of Antarctic krill, sampled during two campaigns in the Antarctic summer and autumn. A significant proportion of the detected coenzyme A thioesters were associated with the β-oxidation of fatty acids and, consequently, with lipid metabolism. Propionyl-CoA was particularly abundant in samples from the digestive gland, while malonyl- and succinyl-CoA were more prevalent in stomach and hindgut samples. 3-Hydroxy-3-methylglutaryl-CoA, an intermediate in the metabolism of branched amino acids and the biosynthesis of isoprenoids, occurred almost exclusively in the summer samples. Analyzing the free amino acids, very high levels of the non-proteinogenic amino acid sarcosine were found, which possibly serves as an osmolyte for the Antarctic krill and/or plays a role in its digestive process. Among the B vitamins, there were seasonal fluctuations, particularly in B1 and B5. The respiratory quinones exhibited more homogeneous patterns, with UQ10:10 as the dominant representative. These seasonal and organ-dependent variations in the composition of the different metabolite classes can serve as a reference point in future studies to better assess the influence of changing conditions in Antarctic waters.